(untitled) (Acta Scientiarum. Biological Sciences, 2024)
Sweeteners are food additives consumed worldwide, especially by individuals with restrictive diets. This study evaluated the cytotoxic and genotoxic effects of sweeteners widely sold in Brazil through a bioassay with Allium cepa. Onion bulbs were exposed to different concentrations of sweeteners, and their root cells were stained with acetic carmine and analyzed under an optical microscope. Distilled water was used as a negative control, and glyphosate as a positive control. The results demonstrated that the mitotic index (MI) and the chromosome aberration index (CAI) of the three sweeteners tested did not differ significantly from the negative control, indicating that they are not toxic or mutagenic additives. This result is positive for consumers of these products, especially those who need to replace sugar due to dietary restrictions. However, they should be consumed with caution.